2006
DOI: 10.3892/or.15.6.1417
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase expression in oral squamous cell carcinoma predicts response to S-1

Abstract: Abstract. The purpose of this research was to evaluate the predictive value of expression of thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD), thymidine phosphorylase (TP), or orotate phosphoribosyltransferase (OPRT) genes for response to S-1. Twenty-five patients with oral squamous cell carcinoma (OSCC) received S-1 80 mg/m 2 /day. Pretreatment tumor biopsies were analyzed for TS, DPD, TP or OPRT mRNA expression by real-time reverse transcription-PCR. TS protein expression was evaluated by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This complex inhibits the conversion of deoxyuridine monophosphate to deoxythymidine monophosphate, which is an essential step of DNA synthesis, thus exerting anticancer effects (2). Consequently, the overexpression of TS possibly decreases the inhibitory effect of 5-FU on DNA synthesis; several studies suggested that high amounts of TS in tumor cells may decrease the efficiency of 5-FU and lead to the development of drug resistance (3)(4)(5)(6)(7). DPD is the initial and rate-limiting enzyme in the catabolic pathway of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This complex inhibits the conversion of deoxyuridine monophosphate to deoxythymidine monophosphate, which is an essential step of DNA synthesis, thus exerting anticancer effects (2). Consequently, the overexpression of TS possibly decreases the inhibitory effect of 5-FU on DNA synthesis; several studies suggested that high amounts of TS in tumor cells may decrease the efficiency of 5-FU and lead to the development of drug resistance (3)(4)(5)(6)(7). DPD is the initial and rate-limiting enzyme in the catabolic pathway of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…1). Thus, the anticancer effects of 5-FU are closely correlated with the activity of its metabolic enzymes, which have been extensively investigated in oral cancers (3,4,8,9,11,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In OSCCs, TS expression, but not TS, DPD or OPRT expression, was shown to predict the response to S-1 [30]. Kobayashi et al reported that DPD expression may provide a clue to predicting the sensitivity to 5-FU in patients with OSCC [29].…”
mentioning
confidence: 99%